True Eye Emergencies - Astari, Dewanti Widya; Muslima, Patriotika; Utami, Putri; Putri, Kreati Hanna; Febrian, Ilham Rohmat; Widayanti, Amanda; Amajida, Saraya; Setiadi, Diaz Hazrina; Octaviany, Efi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Eye emergency is an eye emergency where a condition requires immediate medical attention due to sudden changes in eye health or vision. This case series aims to determine various cases of eye emergencies. The method used is a descriptive case series report design based on true eye emergency case in tertiary referral hospital. The sampling technique used was accidental sampling with the respondents being emergency department patients, totaling 8 respondents. Data was obtained by observation, interviews and participant observation. Management is traced from anamnesis to evaluation. The eye emergencies cases included are chemical trauma, penetrating trauma, endophthalmitis, acute attack glaucoma, open trauma of the eyeball, central retinal artery occlusion, corpus alienum, and mechanical trauma. Handling eye emergencies focuses on precision, accuracy and response time.